STRATEGI PENGEMBANGAN KEPEMIMPINAN DI LEMBAGA PENDIDIKAN ISLAM - A'an Yusuf Khunaifi (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This study explores the significance of strategic leadership development within Islamic educational institutions as a key factor in enhancing management effectiveness and educational quality. Utilizing library research methods, various leadership development strategies were identified, including training, stakeholder engagement, integration of Islamic values, team empowerment, technology utilization, and case studies. Program evaluations indicate that school leaders who internalize modern leadership concepts can foster an inclusive work culture and improve student academic performance. The findings emphasize the need for ongoing strategic initiatives to achieve institutional vision and produce graduates who excel in both knowledge and Islamic values.